Severe Respiratory Acidosis in Acute Exacerbation COPD, Is that Possible to Treat? - Siti Wahdiyati; Limalvin, Nicholas Prathama; Maulidiyah, Novita; Limantara, Ferry; Kurniawan, Fajar (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2024)
Introduction: Chronic obstructive pulmonary disease (COPD), currently the third leading cause of death worldwide, is a common condition characterized by progressive airflow limitation and tissue destruction. Patients with COPD may present to the Emergency Room (ER) with severe acute exacerbations (AECOPD), which can be associated with acute respiratory failure—a life-threatening condition with a mortality rate approaching 50% in Indonesia—requiring rapid intervention and ICU admission. In this report, we present a severe respiratory acidosis in AECOPD case with successful emergency followed by ICU management and the frequent pitfalls. Case Illustration: In this report we present a-67 years old male, pedicab driver and smoker came to the ER with acute onset shortness of breath and decrease of consciousness with history of shortness of breath in last 10 years. In primary survey we found clear wheezing sound, tachypnea, intercostal retraction, decrease of peripheral oxygen saturation, tachycardia and verbal respond of consciousness. Blood gas analysis result interpreted severe respiratory acidosis with pH 6.90 and pCO2 128.5 mmHg. Chest radiograph showed infiltrate that became the cause of exacerbation. Endotracheal intubation was performed due to decreased consciousness, persistent tachypnea and pCO2 over 100 mmHg. This patient was hospitalized for 12 days including 9 days in ICU followed by 3 days in regular ward. Conclusion: The goal for AECOPD management is to minimize and prevent the negative effects of the exacerbation.